THE ROLE OF MANAGEMENT AND HUMAN RESOURCES IN POST-PANDEMIC TOURISM RECOVERY: A CASE STUDY OF CIKADONGDONG RIVER TUBING, MAJALENGKA REGENCY - Alhakim, Muhamad Wasi; Wahyuni, Andyna; Maysari, Maysari; Meliyanti, Windi (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
The COVID-19 pandemic has significantly impacted the global tourism industry, including in Indonesia. This research explores the role of human resources (HR) in managing the Cikadongdong River Tubing tourist destination in the post-pandemic period. Located at the foot of Mount Ciremai in Majalengka Regency, West Java, this destination faces a range of challenges and opportunities in maintaining employee welfare, sustaining productivity, and ensuring operational continuity. Using a qualitative approach, this research includes field observations and in-depth interviews with the head of the Cikadongdong River Tubing management team. The findings reveal that both managers and local HR play a critical role in attracting tourists by enhancing facilities and implementing stringent health protocols. Notable improvements include the construction of two gazebos, the addition of six shower and changing rooms, the renovation of three restrooms, the expansion of parking areas, and the installation of two hand-washing stations. The primary challenge is revitalizing tourist interest and adapting to behavioral shifts that prioritize safety and cleanliness. Supporting factors include improved cleanliness and safety standards, effective environmental management, and innovations in the tourism experience.